Wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating
By printing CoCrFeNiMoTi high-entropy alloy coating on TA15 titanium alloy substrate, the problems of excessive thickness of high-entropy alloy coating and layered wear on the surface of TA15 alloy are solved, and the super-hardness, wear resistance and corrosion resistance are achieved. Thin coating.
Patent Information
- Application Number
- CN202411673487.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
Existing high entropy alloy coatings are too thick, limiting their application in friction, and the low hardness and high viscosity of TA15 alloys lead to surface layering and adhesion wear.
Using commercially used CoCrFeNiMo high-entropy alloy powder with equal atomic ratio, the wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating was printed on the surface of the TA15 titanium alloy substrate through laser melting and deposition and substrate preheating. It was printed with a snake-shaped reciprocating single layer. Method to realize the preparation of ultra-thin coating.
The prepared high-entropy alloy coating has excellent wear resistance and corrosion resistance, the microhardness can reach 889.8HV, and there is no defect such as cracks, pores, etc. It is well-combined with TA15 titanium alloy substrate metallurgy and has a wide range of applications. prospect.
Smart Images

Figure CN119465138A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating, and specifically belongs to the technical field of laser additive manufacturing. Background Art
[0002] High entropy alloys are composed of five or more main elements, which changes the construction system of traditional alloys with one or two metal elements. Compared with traditional alloys, high entropy alloys have better performance, mainly reflected in corrosion resistance, hardness and strength, wear resistance, high temperature oxidation resistance, etc. Due to the excellent performance and broad application prospects of high entropy alloys, its corrosion resistance, hardness and wear resistance are worth exploring. The addition of Mo element to CoCrFeNi high entropy alloys can significantly enhance its mechanical and corrosion properties. From the perspective of mechanical properties, the addition of Mo can lead to a variety of strengthening mechanisms, including solid solution strengthening, precipitation strengthening and dislocation density strengthening. Mo elements with larger atomic size will cause severe lattice distortion, thus showing obvious solid solution strengthening. When Ti elements are added to CoCrFeNi high entropy alloys, the lattice will also be severely distorted, thereby changing the original lattice structure and improving the strength and hardness of the alloy. In addition, the potential of Ti element is relatively positive, and it is easy to form a passivation film with strong corrosion resistance, which prolongs the passivation interval and improves the corrosion resistance of the alloy. Therefore, CoCrFeNiMoTi high entropy alloy composed of Mo and Ti elements may be regarded as an attractive candidate coating material for wear and corrosion resistance.
[0003] In recent years, the preparation and performance of high entropy alloy coatings on ordinary substrates have attracted widespread interest and attention. Such coatings can greatly reduce material costs and exhibit excellent performance. For example, TA15 alloy is a near-α-type titanium alloy that has been widely used in aviation and aerospace engineering due to its excellent properties, such as low density, high specific strength, good high-temperature performance and excellent corrosion resistance. However, due to the low hardness and high viscosity of TA15 alloy, severe delamination and adhesive wear will occur on its surface during friction, which limits its further application. Since high entropy alloys exhibit excellent comprehensive properties, the CoCrFeNiMoTi high entropy alloy coating prepared on the surface of ordinary substrates (such as TA15 alloy) is suitable as a wear-resistant and corrosion-resistant candidate coating material.
[0004] At present, laser additive manufacturing technology has become one of the hot research directions in the field of high entropy alloy coating preparation at home and abroad. Among them, laser cladding technology has been widely used to prepare high entropy alloy coatings. However, the thickness of high entropy alloy coatings prepared by laser cladding is at the millimeter level, and the thickness of high entropy alloy coatings is too thick, which will limit its further application. Compared with laser cladding technology, laser melting deposition adopts a synchronous powder feeding method, combined with substrate preheating treatment, and can achieve the preparation of ultra-thin coatings through serpentine reciprocating single-layer printing, and its powder utilization rate is high. In addition, the coating prepared by laser melting deposition has good metallurgical bonding with the substrate, dense and fine structure, and low dilution rate. Summary of the invention
[0005] In view of the above problems, the present invention proposes a method for preparing a wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating.
[0006] The wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating of the present invention uses commercial CoCrFeNiMo high-entropy alloy powder with an equiatomic ratio as a powder raw material, uses TA15 titanium alloy as a substrate, and prints the wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating on the surface of the substrate by means of laser melting deposition and substrate preheating, and a serpentine reciprocating single-layer printing method. The specific steps are as follows: Step 1: drying the commercial CoCrFeNiMo high entropy alloy powder with equal atomic ratio under vacuum at 110-130° C. for 1-3 hours, and setting it aside as a powder raw material; Step 2: Use 320-mesh, 600-mesh, and 1000-mesh sandpaper to polish the substrate to make it bright and smooth, then place it in anhydrous ethanol for ultrasonic cleaning, and then dry it for later use; Step 3: Place the powder raw material in a powder feeder for stirring and powder feeding, and then place the substrate on an electromagnetic eddy current heater platform for preheating; Step 4: Under the protection of argon, the powder raw material is delivered to the surface of the substrate, and a serpentine reciprocating single-layer printing method is adopted. Through laser melting deposition, the substrate preheating treatment temperature is maintained until the laser melting deposition is completed, and a wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating is obtained.
[0007] The particle size of the CoCrFeNiMo high entropy alloy powder is 15 to 53 μm.
[0008] The temperature of the preheating treatment is 520-580°C.
[0009] The process parameters of the laser melting deposition are: spot diameter of 1.8-2.4 mm, overlap of 0.4-0.8 mm, synchronous powder feeding speed of 0.18-0.22 r / min, powder feeding gas flow rate of 6-8 L / min, scanning speed of 800-1200 mm / min, and laser power of 600-1200 W.
[0010] Beneficial effects of the present invention: 1. The wear-resistant and corrosion-resistant high-entropy alloy coating of the present invention is composed of three BCC (body-centered cubic) solid solution phases. The BCC phase is a high-hardness structure, which is beneficial to improving the mechanical properties of the coating.
[0011] 2. The alloy powder components of the present invention are selected from Co, Cr, Fe, Ni and Mo elements. The dilution of the coating by laser melting deposition will diffuse the matrix Ti element into the coating. The solid solution of Ti element and the high entropy alloy coating can enhance the ability of the coating to form a corrosion-resistant passivation film, thereby effectively improving the corrosion resistance of the coating while improving the hardness of the coating.
[0012] 3. The high entropy alloy coating of the present invention has no defects such as cracks and pores, has good metallurgical bonding with the TA15 titanium alloy substrate, has a dense and fine structure, and a low dilution rate. The microhardness of the coating can reach 889.8HV, has excellent wear resistance and corrosion resistance, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 : SEM morphology of CoCrFeNiMo high entropy alloy powder in Example 1 of the present invention; Figure 2 : XRD phase analysis of the high entropy alloy coating in Example 1 of the present invention; Figure 3-1 : A high-magnification SEM morphology of the upper cross-section of the high entropy alloy coating deposited at 800W in Example 1 of the present invention; Figure 3-2 : A high-magnification SEM morphology of the cross-section of the upper layer of the high-entropy alloy coating deposited at 1000W in Example 1 of the present invention; Figure 3-3 : A high-magnification SEM morphology of the upper cross-section of the high entropy alloy coating deposited at 1200W in Example 1 of the present invention; Figure 4 : Low magnification SEM morphology of a cross section of the high entropy alloy coating in Example 2 of the present invention; Figure 5 : High-magnification SEM morphology of the cross-section of the upper layer of the high-entropy alloy coating in Example 2 of the present invention; Figure 6 : Comparison of the average microhardness of the high entropy alloy coating in Example 2 of the present invention; Figure 7: Comparison of the specific wear rate of the high entropy alloy coating in Example 2 of the present invention; Figure 8 : Potentiodynamic polarization curve of the high entropy alloy coating in Example 2 of the present invention. Specific implementation methods
[0014] In the embodiment, a micro Vickers hardness tester (HVD-10AP) is used to test the microhardness of the high entropy alloy coating. The applied load pressure is 1000 gf, and the holding time is 15 s. The unit of the hardness value is recorded as HV1. Each sample is tested 10 times, and the average value is taken after removing the maximum and minimum values.
[0015] In the embodiment, a ball-disc wear tester (HT-1000) was used to test the friction and wear resistance of the high entropy alloy coating. A GCr15 steel ball with a diameter of 6 mm was selected as the friction pair, and the wear time, load, radius and spindle speed were set to 60 min, 15 N, 5 mm and 500 r / min respectively. Each sample was tested three times. Then, a profilometer (JB-5C) was used to test the cross-sectional profile of the coating after wear, and then the specific wear rate value was calculated.
[0016] In the embodiment, an electrochemical workstation (REF3000-32117) was used to test the electrochemical resistance of the high entropy alloy coating. The test environment was room temperature, 3.5wt% NaCl solution, a classic three-electrode cell was used, the auxiliary electrode was a 10mm×10mm platinum sheet, the reference electrode was a saturated calomel electrode, and the sample size was 7mm×7mm×4mm.
[0017] Example 1 The preparation process of the CoCrFeNiMoTi high entropy alloy coating in this embodiment includes the following steps: Step 1: Select commercial CoCrFeNiMo high entropy alloy powder with a particle size of 15 to 53 μm and an equal atomic ratio as a powder raw material; place the CoCrFeNiMo high entropy alloy powder in a vacuum drying oven at a temperature of 120° C. for vacuum drying for 2 hours to obtain a powder raw material for laser melting deposition.
[0018] Step 2: Select a TA15 titanium alloy circular plate with a size of Φ30mm in diameter and 10mm in thickness as the printing substrate. Use 320-mesh, 600-mesh, and 1000-mesh sandpaper to polish the TA15 titanium alloy substrate to make it bright and smooth. Then place it in an anhydrous ethanol solution for ultrasonic cleaning of the surface. Take it out and place it in an oven to dry for later use.
[0019] Step 3: Before printing, the high entropy alloy powder raw material is placed in a powder feeder for stirring and powder feeding, and the TA15 titanium alloy substrate is preheated to 570°C. Then, the alloy powder raw material is sent to the surface of the TA15 titanium alloy substrate through the protective argon gas using the LDM 8060 powder feeding metal-based composite laser rapid prototyping machine. Through the serpentine reciprocating single-layer printing method, the laser beam directly melts and deposits to obtain the high entropy alloy coating. During the laser printing process, the preheating temperature is maintained until the laser melting and deposition of the high entropy alloy coating is completed. After the printing is completed, the sample is slowly cooled to room temperature along with the heating plate.
[0020] The laser printing parameters are as follows: laser spot diameter is 2.0 mm, overlap is 0.6 mm, synchronous powder feeding speed is 0.18 r / min, powder feeding gas flow rate is 10 L / min, scanning speed is 1000 mm / min, and laser power is 800 W, 1000 W and 1200 W.
[0021] Step 4: Use a wire cutting machine to cut the sample prepared in step 3 along the cross-sectional direction of the coating, and then grind and polish it with 320 to 2000 mesh metallographic sandpaper in turn. Observe the cross-sectional morphology of the coating. The coating has no obvious defects such as holes and cracks, and is well bonded to the TA15 titanium alloy substrate.
[0022] The SEM morphology of the high entropy alloy powder in the embodiment of the present invention is as follows: Figure 1 As shown in FIG. 1 , the powder is spherical powder with high fluidity. The XRD results of the high entropy alloy coating deposited by laser melting at different powers in the embodiment of the present invention are shown in FIG. Figure 2 As shown, the main components of the coating are BCC1, BCC2 (face-centered cubic) and B2 (ordered body-centered cubic) solid solution phases. The high-magnification scanning electron microscope images of the upper layer of the cross-section of the high-entropy alloy coating deposited by laser melting at 800W, 1000W and 1200W in Example 1 of the present invention are shown in Figure 3. The microstructure of the coating is characterized by a dark gray B2 solid solution phase uniformly distributed between the light gray BCC1 main phases, and the bright white phase is the BCC2 solid solution phase.
[0023] Example 2 The preparation process of the wear-resistant and corrosion-resistant CoCrFeNiMoTi high entropy alloy coating in this embodiment includes the following steps: Step 1: Select an equiatomic ratio CoCrFeNiMo high entropy alloy commercial powder with a particle size of 15 to 53 μm as a powder raw material; weigh an appropriate amount of CoCrFeNiMo high entropy alloy powder and place it in a vacuum drying oven at a temperature of 120° C. for vacuum drying for 2 hours to obtain a laser melting deposition alloy powder.
[0024] Step 2: Select a TA15 titanium alloy circular plate with a size of Φ30mm in diameter and 10mm in thickness as the printing substrate. Use 320-mesh, 600-mesh, and 1000-mesh sandpaper to polish the TA15 titanium alloy substrate to make it bright and smooth. Then place it in an anhydrous ethanol solution for ultrasonic cleaning of the surface. Take it out and place it in an oven to dry for later use.
[0025] Step 3: Before printing, the high entropy alloy powder raw material is placed in a powder feeder for stirring and powder feeding, and the TA15 titanium alloy substrate is preheated to 570°C. Then, the alloy powder raw material is sent to the surface of the TA15 titanium alloy substrate through the protective argon gas using the LDM 8060 powder feeding metal-based composite laser rapid prototyping machine. Through the serpentine reciprocating single-layer printing method, the laser beam directly melts and deposits to obtain the high entropy alloy coating. During the laser printing process, the preheating temperature is maintained until the laser melting and deposition of the high entropy alloy coating is completed. After the printing is completed, the sample is slowly cooled to room temperature along with the heating plate.
[0026] The laser printing parameters are as follows: laser spot diameter is 2.0 mm, overlap is 0.6 mm, synchronous powder feeding speed is 0.18 r / min, powder feeding gas flow rate is 10 L / min, scanning speed is 1000 mm / min, and laser power is 600 W.
[0027] Step 4: Use a wire cutting machine to cut the sample prepared in step 3 along the cross-sectional direction of the coating, and then grind and polish it with 320 to 2000 mesh metallographic sandpaper in turn. Observe the cross-sectional morphology of the coating. The coating has no obvious defects such as holes and cracks, and is well bonded to the TA15 titanium alloy substrate.
[0028] The XRD results of the CoCrFeNiMoTi high entropy alloy coating in Example 2 of the present invention are as follows: Figure 2 As shown in FIG. 1 , the main components of the high entropy alloy coating are also BCC1, BCC2 (face-centered cubic) and B2 (ordered body-centered cubic) solid solution phases. The low-magnification scanning electron microscope image of the cross section of the CoCrFeNiMoTi high entropy alloy coating in Example 2 of the present invention is shown in FIG. Figure 4 As shown in the figure, it can be seen that the coating has no defects such as cracks and pores, and has good metallurgical bonding with the TA15 titanium alloy substrate. The high-magnification scanning electron microscope image of the upper layer of the high-entropy alloy coating cross section is shown in Figure 5 As shown in the figure, the light gray phase is the BCC1 main phase, the dark gray phase is the B2 solid solution phase, and the bright white phase is the BCC2 solid solution phase. According to the three-phase energy spectrum (EDS) data in Table 1, the main phase BCC1 phase has uniform element distribution. Correspondingly, the BCC2 phase is rich in Mo and Cr elements, while the B2 phase is poor in Mo and Cr elements.
[0029] The microhardness test results of the high entropy alloy coating in Example 2 of the present invention are as follows: Figure 6 As shown. Figure 6It can be seen that the high entropy alloy coating deposited at a laser power of 600W has a higher Vickers hardness (up to 889.8HV1).
[0030] The friction and wear test results of the high entropy alloy coating in Example 2 of the present invention are as follows: Figure 7 Compared with Example 1, the high entropy alloy coating deposited at a laser power of 600 W achieved the lowest specific wear rate (2.9×10 -5 mm 3 / (N·m)), showing excellent wear resistance.
[0031] The electrochemical corrosion performance test results of the high entropy alloy coating in Example 2 of the present invention are as follows: Figure 8 As shown in the figure, it can be seen from the potentiodynamic polarization curve of the high entropy alloy coating that the self-corrosion potential of the high entropy alloy coating is relatively positive and the self-corrosion current density is low. The corrosion current density of the CoCrFeNiMoTi high entropy alloy coating is the lowest. , the high entropy alloy coating has excellent corrosion resistance.
[0032] .
Claims
1. A wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating, characterized in that: The high entropy alloy coating is made of commercial CoCrFeNiMo high entropy alloy powder with an equiatomic ratio as powder raw material, TA15 titanium alloy as substrate, and a wear-resistant and corrosion-resistant CoCrFeNiMoTi high entropy alloy coating is printed on the substrate surface by laser melting deposition and substrate preheating, and a serpentine reciprocating single-layer printing method. The specific steps are as follows: Step 1: drying the commercial CoCrFeNiMo high entropy alloy powder with equal atomic ratio under vacuum at 110-130° C. for 1-3 hours, and setting it aside as a powder raw material; Step 2: Use 320-mesh, 600-mesh, and 1000-mesh sandpaper to polish the substrate to make it bright and smooth, then place it in anhydrous ethanol for ultrasonic cleaning, and then dry it for later use; Step 3: Place the powder raw material in a powder feeder for stirring and powder feeding, and then place the substrate on an electromagnetic eddy current heater platform for preheating; Step 4: Under the protection of argon, the powder raw material is delivered to the surface of the substrate, and a serpentine reciprocating single-layer printing method is adopted. Through laser melting deposition, the substrate preheating treatment temperature is maintained until the laser melting deposition is completed, and a wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating is obtained.
2. The wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating according to claim 1, characterized in that: The particle size of the CoCrFeNiMo high entropy alloy powder is 15 to 53 μm.
3. The wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating according to claim 1, characterized in that: The temperature of the preheating treatment is 520-580°C.
4. The wear-resistant and corrosion-resistant CoCrFeNiMoTi high-entropy alloy coating according to claim 1, characterized in that: The process parameters of the laser melting deposition are: spot diameter of 1.8-2.4 mm, overlap of 0.4-0.8 mm, synchronous powder feeding speed of 0.18-0.22 r / min, powder feeding gas flow rate of 6-8 L / min, scanning speed of 800-1200 mm / min, and laser power of 600-1200 W.